Use of injectable hormonal contraception and women's risk of herpes simplex virus type 2 acquisition: a prospective study of couples in Rakai, Uganda. Issue 8 (August 2015) - Grabowski, Mary K; Gray, Ronald H; Makumbi, Fred; Kagaayi, Joseph; Redd, Andrew D; Kigozi, Godfrey; Reynolds, Steven J; Nalugoda, Fred; Lutalo, Tom; Wawer, Maria J; Serwadda, David; Quinn, Thomas C; et al.
Summary Background The injectable hormonal contraceptive depo-medroxyprogesterone acetate (DMPA) has been associated with increased risk of HIV acquisition, but findings are inconsistent. Whether DMPA increases the risk of other sexually transmitted viral infections is unknown. We assessed the association between DMPA use and incident herpes simplex virus type 2 (HSV2) infection in women. Methods In this prospective study, we enrolled HIV-negative and HSV2-negative women aged 15–49 years whose HIV-negative male partners were concurrently enrolled in a randomised trial of male circumcision in Rakai, Uganda. We excluded women if either they or their male partners HIV seroconverted. The primary outcome was HSV2 seroconversion, assessed annually. The male circumcision trial was registered with ClinicalTrials.gov, number NCT00425984. Findings Between Aug 11, 2003, and July 6, 2006, we enrolled 682 women in this study. We noted HSV2 seroconversions in 70 (10%) women. Incidence was 13·5 per 100 person-years in women consistently using DMPA (nine incident infections per 66·5 person-years), 4·3 per 100 person-years in pregnant women who were not using hormonal contraception (18 incident infections per 423·5 person-years), and 6·6 per 100 person-years in women who were neither pregnant nor using hormonal contraception (35 incident infections per 529·5 person-years). Women consistently using DMPA had an adjusted hazard ratio for HSV2 seroconversion of 2·26 (95% CI 1·09–4·69; p=0·029) compared with women who were neither pregnant nor using hormonal contraception. Of 132 women with HSV2-seropositive partners, seroconversion was 36·4 per 100 person-years in consistent DMPA users (four incident infections per 11 person-years) and 10·7 per 100 person-years in women who were neither pregnant nor using hormonal contraception (11 incident infections per 103 person-years; adjusted hazard ratio 6·23, 95% CI 1·49–26·3; p=0·012). Interpretation Consistent DMPA use might increase risk of HSV2 seroconversion; however, study power was low. These findings should be assessed in larger populations with more frequent follow-up than in this study, and other contraceptive methods should also be assessed. Access to a wide range of highly effective contraceptive methods is needed for women, particularly in sub-Saharan Africa. Funding Bill and Melinda Gates Foundation, Doris Duke Charitable Foundation, US National Institutes of Health, and Fogarty International Center.